A conductive interwoven bamboo carbon fiber membrane for Li–S batteries1. Issue 18 (14th May 2015) - Gu, Xingxing; Lai, Chao; Liu, Fei; Yang, Wenlong; Hou, Yanglong; Zhang, Shanqing
<x xml:space="preserve">Abstract</x> Natural bamboo, as a sustainable precursor, is used to prepare porous bamboo carbon fibers (BCFs) that are subsequently interwoven into a BCF membrane (BCFM) as a captor interlayer for the lithium polysulfide intermediates between the sulfur cathode and the separator in Li–S batteries.